Engaging with nature and work: associations among the built and natural environment, experiences outside, and job engagement and creativity - Brossoit, Rebecca M.; Crain, Tori L.; Leslie, Jordyn J.; Fisher, Gwenith G.; Eakman, Aaron M. (Frontiers in Psychology, 2024)
There is substantial evidence that contact with nature is related to positive health and well-being outcomes, but extensions of this research to work-related outcomes is sparse. Some organizations are redesigning workspaces to incorporate nature and adopting nature-related policies, warranting a need for empirical studies that test the influence of nature on employee outcomes. The present mixed-methods study tests and extends the biophilic work design model to examine associations among the built and natural environment at work and home, experiences of time spent outside (i.e., amount of time outside, enjoyment of time outside, outdoor activities), and motivational work outcomes (i.e., job engagement and creativity). Objective geographic data were combined with quantitative and qualitative survey responses from working adults (N = 803). Our results broadly indicate that individuals who work and live in areas with greater natural amenities (i.e., access to water, topographic variation, temperate climates) spend more time outside and enjoy time outside to a greater degree, and these experiences are in turn associated with greater engagement and creativity at work. We did not find evidence that the surrounding built environment (i.e., urbanity) at work or home was associated with outdoor experiences or work-related outcomes. These findings provide evidence that the natural environment, particularly at home, can benefit work-related outcomes via greater time and enjoyment of time outside. Additionally, six categories of outdoor activities were identified in the qualitative analyses (i.e., leisure activities, relaxation, physical activities, social interactions, tasks and errands, and travel), and have unique associations with the key variables. This study has implications for employee time use and organizational effectiveness.